Depth-dependent peridotite-melt interaction and the origin of variable silica in the cratonic mantle - Emma L. Tomlinson (Nature Portfolio, 2021)
The compositional variability amongst Archaean cratonic peridotites has long been recognized, however its origin remains debated. The authors here find that the collapse of the dual Archaean mantle melting environment ceased production of silica-enriched mantle lithosphere.